PEMAKNAAN KHALAYAK TERHADAP FILM “MARLINA SI PEMBUNUH DALAM EMPAT BABAK” - Andrew Manogu N; Sri Budi Lestari (Interaksi Online, 2019)
This research is motivated by the presence of feminist films in the midst of the development of mainstream films (men as the main actors). So far women have decided as a complement to the story because of gender injustice caused by gender differences. The film "Marlina the Killer in Four Acts" is a film that shows women leaders who contradict the mainstream film that is developing at this time, with the aim of criticizing the dominance of patriarchy that is developing at this time. This different film theme supports researchers to complete the various meanings given by the general public with different backgrounds to this film using Ien Ang's acceptance analysis. Before analyzing the meanings given by audiences, researchers uncovered the reading choices offered by this film using Roland Barthes's semiotics. Some scenes in this film show the position of women who are oppressed but can provide limits. The preferred form of oppression is from patriarchal domination which asks women for men. While fighting against what is won by women is by completing their possessions and breaking this dominance by utilizing women's weaknesses into strengths. The audiences as producers of meaning provide diverse experiences. Inform information about this film women improve repression that is detrimental to them. Then two out of four Infromans did not agree with the method given by the women in the film. One other informant agreed with how to approve the given, while the other informants agreed not to agree with him because the actions of women in the film opposed the law as well as the prevailing norms.